Pro-environmental behavior as a means of self-signaling: Theory and evidence - Flörchinger, Daniela; Frondel, Manuel; Sommer, Stephan; Andor, Mark A. (Technische Universität Dortmund, 2022)
Recent research indicates that pro-environmental behavior may be driven by concerns about one’s moral identity. Using identiﬁcation with the environmentalist movement Fridays for Future, this paper develops and empirically tests a straightforward model of self-signaling. We assume that pro-environmental behavior, here taking the train rather than the plane for a journey, serves as a means of self-signaling. On the basis of a large-scale survey experiment with revealed preferences, we ﬁnd evidence that respondents who receive an identity prime in the form of a reminder of their previously stated attitude towards Fridays for Future are more likely to behave in line with the movement’s moral principles in that they take the train. Our explanation of this outcome is that individuals attempt to avoid cognitive dissonance by choosing the more environmentally benign alternative. Our results suggest that pro-environmental behavior may be enhanced by appealing to an individual’s self-image so that costly interventions that are designed to convince subjects of new moral principles may be unnecessary.
Discussion Paper / SFB823;31/2021
Keywords: pro-social behavior; self-signaling; cognitive dissonance; moral identity; 310; 330; 620